Miasto w Lailonii. Uwagi scenarzysty - Zamojski, Jan (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2013)
A city in Lailonia. Remarks from a screenwriter The article discusses the role of the city in Tales from the Kingdom of Lailonia by the philosopher Leszek Kołakowski, and in the animated film series Fourteen Tales from the Kingdom of Lailonia by Leszek Kołakowski, which is an adaptation of the book. The article is written from the point of view of the originator of the adaptation and the screenwriter of all the films in the series. The author examines the historical and ideological context of L. Kołakowski’s writing the Tales … and analyzes the role of the city understood as the setting of the plot (topos) and the venue for an exchange of ideas (agora) and for the community (polis); he does so on three levels: that of the literary original, the screenplay adaptation, and the film. He also examines the role of the city in those senses for the drama of the individual films, the philosophical and esthetic premises of the role, and – in these contexts – the relations between the selected films and their screenplays.